Pemanfaatan Aplikasi Web Untuk Pengarsipan Elektronik Guna Meningkatkan Efisiensi Administrasi SMK Triguna 1956 Jakarta - Achmad Syarif; Laras Shinta Frameswari; Vicky Mulia Sheiren (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Archive management in Vocational High Schools (SMK) often faces serious constraints related to the uncontrolled accumulation of physical documents and the difficulty of information retrieval. SMK Triguna 1956 Jakarta, a vocational institution focusing on accounting and office management, requires a more agile system to manage teaching materials, student data, and other administrative documents. This community service activity aims to provide training and mentoring for teachers in implementing web-based electronic archiving applications. The methods used include situational analysis, 42 hours of intensive training, practical demonstrations, and evaluation through pre-test and post-test. The results showed a significant increase in the digital competence of participants, where the understanding of archival concepts increased by 18% and technical system operation skills increased by up to 80%. The implementation of this web-based system is proven to accelerate document retrieval time from hours to seconds and ensure data security through encryption and access control. The conclusion of this activity confirms that archive digitalization is not just a transition of media, but a transformation of work culture towards an educational ecosystem that is more accountable, efficient, and environmentally friendly.